A Network Conceptualization of Team Conflict - Park, Semin; Mathieu, John E.; Grosser, Travis J. (Academy of Management Review, 2020)
Previous research has highlighted how interpersonal- and task-based conflicts can impact work team effectiveness. The majority of such work, however, has implicitly treated both types of conflict as shared team properties. Yet each team member may perceive or experience varying degrees of conflict with other team members, suggesting that individuals may have unique conflict experiences. Moreover, individual members may interact differently with each other on task assignments, which leads to a complex interplay between task flow and conflict relations. Therefore, we propose a more fine-grained theoretical conception of conflict dynamics as multiplex network configurations in conjunction with task flow interdependencies. Dyadic tie configurations of conflict and task relations generate different interpersonal dynamics, which, in turn, affect overall task effectiveness. As a way of bypassing dysfunctional conflict relations, members may pursue workarounds, which result in deviations from optimal task flow patterns and have implications for overall team effectiveness. Finally, we discuss the implications of the network conceptualization with three illustrative network configurations that may arise from different combinations of dyadic patterns and conclude with theoretical, methodological, and practical implications of adopting this multiplex network conception.